The loyalty of workers to industrial organization - Ernayani, Rihfenti; Perbawasari, Susie; Boukri, Soukaina; Hubur, Aa; Kurniawan, Roan (Linguistics and Culture Review, 2021)
The differences in roles between individuals in Western factories and in Japanese factories - the ways in which individuals are given responsibility and authority, what rewards are given, and behaviors are rewarded - have a close relationship with the differences between their two cultural backgrounds. Japanese industry has for decades coated the top of a very and once feudal society for several centuries. The loyalty of workers to industrial organization, the paternal style of motivating and paying workers, the deep involvement of the company in all things which were to the eyes of the workers’ private affairs - all of these had something in common with Japanese pre-industrial social organization. This equation does not underestimate the massive changes that have taken place in Japan during its industrialization period. Japan has changed enormously; and the changes continue. However, if the study of industrialization in Japan is to be relevant for the study of economic development in other Asian nations, then the nature of the changes that have occurred must be well understood.